ΑVβ5 and CD44 Are Oxygen-Regulated Human Embryonic Stem Cell Attachment Factors. (26th December 2013) - Kumar, Deepak; Gupta, Saniya; Yang, Ying; Forsyth, Nicholas R.
Abstract : Human embryonic stem cells (hESCs) have great potential for clinical therapeutic use. However, relatively little is known of the mechanisms which dictate their specificity of adhesion to substrates through adhesion proteins including integrins. Previous observations demonstrated enhanced clonogenicity in reduced oxygen culture systems. Here, we demonstrated via antibody blocking experiments that α V β 5 and α 6 significantly promoted hESC attachment in 2% O2 only, whereas blockage of CD44 inhibited cell attachment in 21% O2 alone. Immunofluorescence confirmed expression of α V β 5 and CD44 in both 2% O2 and 21% O2 cultured hESCs while flow cytometry revealed significantly higher α V β 5 expression in 2% O2 versus 21% O2 cultured hESCs and higher CD44 expression in 21% O2 versus 2% O2 cultured hESCs. Adhered hESCs following blockage of α V β 5 in 2% O2 displayed a reduction in nuclear colocalisation of Oct-4 and Nanog with little effect observed in 21% O2 . Blockage of CD44 had the converse effect with dramatic reductions in nuclear colocalisation of Oct-4 and Nanog in 21% O2 cultured hESC which retained adherence, but not in 2% O2 cultured cells. Identification of oxygen-dependent substrate attachment mechanisms in hESCs has the potential to play a role in the development of novel substrates to improve hESC attachment and culture.